Global and target analysis of relaxation processes of the collapsed state of P3HT polymer nanoparticles. Issue 4 (9th January 2020) - Ghosh, Arnab; Ghosh, Srijon; Ghosh, Goutam; Jana, Bikash; Patra, Amitava
Abstract : Organic–inorganic hetero-structures composed of P3HT PNPs and Au NPs have been designed for efficient light harvesting systems. Here electron transfer occurs from vibrationally hot S1 state and delocalized collective state (CLS ) of PNPs to Au NPs. Abstract : Organic–inorganic heterostructure materials have received significant research interest for designing light harvesting devices because of their efficient charge separation. Here, we design organic and inorganic nano-heterostructures using conjugated polymer nanoparticles (PNPs) [poly(3-hexylthiophene-2, 5-diyl), P3HT] and Au nanoparticles. We investigate the carrier relaxation processes of this heterostructure at different time scales by ultrafast transient absorption spectroscopy. The lifetime of the singlet state (S1 ) of the pristine polymer shortens from 480.7 ps to 2.8 ps due to the formation of nanoparticles, and the formation of a delocalized collective state (CLS ) is obtained in polymer nanoparticles whose lifetime is found to be 384.6 ps. The hot and ultrafast electron transfers occur from P3HT polymer nanoparticles to Au nanoparticles and the time constants are 253 fs and 37.7 ps, respectively, which are responsible for the efficient charge separation in such heterostructures. Such a fundamental study of relaxation processes of organic–inorganic nano heterostructures is very significant for designing light harvesting systems.